2009
DOI: 10.1080/08958370802566648
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of air pollution and habitual smoking on the retention of inorganic fibers identified as ferruginous bodies in autopsy cases in Mexico City

Abstract: In order to evaluate the synergistic effect of habitual smoking and air pollution in Mexico City on the retention of inorganic fibers, ferruginous bodies (FB) were quantified as markers of exposure to inorganic fibers in lung digests from 426 autopsy cases. FB were isolated from 426 lung digests from cases with several lung diseases. The results revealed more retention of FB in the smokers group than in non-smokers: 38 FB per gram (FB/g) versus 11.2 FB/g, respectively (p < 0.05). Male smokers living in Mexico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…AB are recognized as FB and are typified by their characteristic appearance under light microscopy: fibers that are straight and transparent. Quantified results show that smokers generally have higher concentrations of AB and FB than nonsmokers (Churg & Warnock, 1977;Arenas-Huertero et al, 1994;Salazar-Flores et al, 2009); in fact, in a study conducted in Mexico based on the evaluation of autopsy cases, Salazar-Flores et al (2009) verified the existence of a synergic effect between air pollution in Mexico City and smoking that led to a high retention of FB, especially among men. In their study, the authors demonstrated that male residents of Mexico City who smoked presented a mean of 54 FB/g (FB per gram of dry tissue), compared to 34 FB/g in nonsmoking men there, and to the 11 FB/g found in nonsmokers in rural areas.…”
Section: Research Articlementioning
confidence: 87%
See 4 more Smart Citations
“…AB are recognized as FB and are typified by their characteristic appearance under light microscopy: fibers that are straight and transparent. Quantified results show that smokers generally have higher concentrations of AB and FB than nonsmokers (Churg & Warnock, 1977;Arenas-Huertero et al, 1994;Salazar-Flores et al, 2009); in fact, in a study conducted in Mexico based on the evaluation of autopsy cases, Salazar-Flores et al (2009) verified the existence of a synergic effect between air pollution in Mexico City and smoking that led to a high retention of FB, especially among men. In their study, the authors demonstrated that male residents of Mexico City who smoked presented a mean of 54 FB/g (FB per gram of dry tissue), compared to 34 FB/g in nonsmoking men there, and to the 11 FB/g found in nonsmokers in rural areas.…”
Section: Research Articlementioning
confidence: 87%
“…This effect of augmenting FB retention is strongly linked to the number of cigarettes smoked, especially when consumption exceeds 300 packs per year. Environmental exposure to asbestos or other, similar, materials also occurs naturally, as shown by the fact that people from rural areas (Breedin & Buss, 1976) may have similar concentrations of FB to those found in nonsmokers in Mexico City (Salazar-Flores et al, 2009). As FB may be present in almost any individual, and given the severity of the problems of pollution in large urban areas like Mexico City, it is important to conduct both descriptive and quantitative studies that will enable us to better understand the possible magnitude of such exposures, gain a clearer idea of their effects, and evaluate the relation between this factor and the incidence of pulmonary disease (Roggli, 2004).…”
Section: Research Articlementioning
confidence: 94%
See 3 more Smart Citations